“Watch and wait” approach in rectal cancer patients following complete clinical response to neoadjuvant chemoradiotherapy does not compromise oncologic outcomes - Neşşar, Gürel; Demirbağ, Ali Eba; Mısırlıoğlu, Hasan Cem; Sezer, Semih (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Although standart treatment for non-metastatic locally advanced rectal cancer includes neoadjuvant chemoradiation followed by surgical resection, patients who have achieved complete clinical response can be followed up without surgery.Materials and Methods: Between 2010 and 2016, 61 patients received neoadjuvant chemoradiotherapy for low rectal cancer. Those patients who achieved clinical complete response were included in the “watch and wait” protocol and did not receive surgery. The remaining patients underwent radical surgery and some of these were diagnosed as having complete response pathologically. This study compared the oncological results of clinically complete responders with those patients defined as pathologically tumor-free.Results: Seven patients who received neoadjuvant chemoradiotherapy were re-staged as having complete clinical response and included in the “watch and wait” approach protocol. The 5-year disease free survival was 100%. Mean follow-up was 63 months and the mean age was 57.3. Fifty-four patients underwent radical surgery and 7 of them were diagnosed as having pathological complete response. The 5-year survival was 100%. Mean follow-up was 56 months and the mean age was 50.6. All patients except one are alive without tumor recurrence in the surgery group. However, those who received surgery experienced significant morbidities due to their surgery.Conclusion: The oncological results of the “watch and wait” approach patients were no different from the patients who received radical surgery and were diagnosed as having pathological complete response. Those patients in particular who required abdomino-perineal resection before chemoradiation should be informed about this approach if they have achieved complete response clinically.